Reluctant Germans: performing identity abroad - Gaude, Thomas Frank Daniel (Social Anthropology, 2025)
This thesis deals with members of a particular age cohort of German migrants in Cape Town. The informants all belong to Germany's 'post-boomer' generation, which has been the subject of much recent popular media coverage in Germany. Similar situations have been portrayed in writings from the USA. Being members of the middle-class, the respondents are equipped with both financial and cultural capital, which facilitates their connectedness to both home country and receiving society while abroad. This form of multiple connectedness implies a transnational identity as described by various authors. The particularity of these respondents' performance of national identity in Cape Town is based on both their perception of, and attitudes towards, Germany as well as the impact of their new surrounding. The perception of their home country is informed through a combination of the informants' upbringing in an era of financial wealth, being part of a particular generation in Germany, and existing stereotypical images of 'Germanness'. In Cape Town these respondents avoid creating an ethnic enclave and distance themselves from the established German community in the city. Instead they seek contact with citizens of other nation-states and engage in behavior that has been deemed 'cosmopolitan'. This cosmopolitanism surfaces in their everyday life in South Africa, in relationship to, for example, their social networks, areas of residence and material culture. Loss of national identity, in this case, is not felt as a painful process as described in most other studies on diasporas, but rather as a willful action.